Proposal for a Context Concept in Delta - Møller-Pedersen, Birger (DAIMI Report Series, 1977)
The description of a context concept in DELTA is analyzed, similar concepts from various fields are considered, and on the basis of this and on the use of a context concept in an application of DELTA in an interdisciplinary project a definition of a context concept is proposed.